EFISIENSI PEMANFAATAN PAKAN DAN PERTUMBUHAN LELE DUMBO (CLARIAS GARIEPINUS) STRAIN SANGKURIANG YANG DIPELIHARA PADA MEDIA DENGAN SALINITAS YANG BERBEDADALAM KOLAM PLASTIK - Ristiawan Agung Nugroho; Diana Chilmawati (Fakultas Perikanan Universitas Pekalongan, 2017)
The experiment to determine the best salinity on media for the efficiency of use of Catfish (Clarias gariepinus) strain Sangkuriang’sfeed and growth. Laboratory experimental was used with various salinity variable were: 0 ‰ (as control), 1 ‰, 2 ‰, 3 ‰, 4 ‰ and 5 ‰ with 3 repetitions for each. 3% for fish weight feeding on twice a day at 8.00 am and 6.00 pm. The result of this research showed that cultured at plastic pond media with different salinity do not have an effects (p > 0,05) to feeding efficiency and daily growth rate of Sangkuriang’s strain of lele dumbo (Clarias gariepinus var.), but it has a significant effect (p<0,01) to absolute biomassa growth, feeding conversion and survival rate. Cultured Sangkuriang’s lele dumbo in plastic pond could be efficiently conducted at media’s salinity up to 5 ‰, but by significant notice at frequency, type and nutritional composition of feeding and also controlling the water quality. The most appropriate optimal salinity value, based from growth of compensation for the rearing of consumption size, is 4 ppm. The water quality showed on supporting life of lele dumbo lele’s cultured in plastic pond.Keyword: Feed, Growth, Sangkuriang’s catfish, salinity, Plastic pond